Phenobarbital but Not Diazepam Reduces AMPA/kainate Receptor Mediated Currents and Exerts Opposite Actions on Initial Seizures in the Neonatal Rat Hippocampus - Nardou, Romain; Yamamoto, Sumii; Bhar, Asma; Burnashev, Nael; Ben-Ari, Yehezkel; Khalilov, Ilgam (Frontiers in Cellular Neuroscience, 2011)
Diazepam (DZP) and phenobarbital (PB) are extensively used as first and second line drugs to treat acute seizures in neonates and their actions are thought to be mediated by increasing the actions of GABAergic signals. Yet, their efficacy is variable with occasional failure or even aggravation of recurrent seizures questioning whether other mechanisms are not involved in their actions. We have now compared the effects of DZP and PB on ictal-like events (ILEs) in an in vitro model of mirror focus (MF). Using the three-compartment chamber with the two immature hippocampi and their commissural fibers placed in 3 different compartments, kainate was applied to one hippocampus and PB or DZP to the contralateral one, either after one ILE or after many recurrent ILEs that produce an epileptogenic MF. We report that in contrast to PB, DZP aggravated propagating ILEs from the start and did not prevent the formation of MF. PB reduced and DZP increased the network driven Giant Depolarising Potentials suggesting that PB may exert additional actions that are not mediated by GABA signalling. In keeping with this, PB but not DZP reduced field potentials recorded in the presence of GABA and NMDA receptor antagonists. These effects are mediated by a direct action on AMPA/Kainate receptors since PB: i) reduced AMPA/Kainate receptor mediated currents induced by focal applications of glutamate ; ii) reduced the amplitude and the frequency of AMPA but not NMDA receptor mediated miniature EPSCs; iii) augmented the number of AMPA receptor mediated EPSCs failures evoked by minimal stimulation. These effects persisted in MF. Therefore, PB exerts its anticonvulsive actions partly by reducing AMPA/Kainate receptors mediated EPSCs in addition to the pro-GABA effects. We suggest that PB may have advantage over DZP in the treatment of initial neonatal seizures since the additional reduction of glutamate receptors mediated signals may reduce the severity of neonatal seizures.